1935
DOI: 10.1152/ajplegacy.1935.114.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Afferent Function in the Group of Nerve Fibers of Slowest Conduction Velocity

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1942
1942
1973
1973

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…By stimulating electrically the central end of the cat's saphenous nerve, and recording the action potential set up, Clark et al (1935) were able to show that the C fibres produced powerful circulatory and respiratory reflexes: they concluded that the non-medullated fibres were involved in signalling pain. Subsequent experiments on humans provided indirect corroborative evidence (see Bishop, 1946;Gasser, 1943;Landau & Bishop, 1953).…”
Section: Discussionmentioning
confidence: 99%
“…By stimulating electrically the central end of the cat's saphenous nerve, and recording the action potential set up, Clark et al (1935) were able to show that the C fibres produced powerful circulatory and respiratory reflexes: they concluded that the non-medullated fibres were involved in signalling pain. Subsequent experiments on humans provided indirect corroborative evidence (see Bishop, 1946;Gasser, 1943;Landau & Bishop, 1953).…”
Section: Discussionmentioning
confidence: 99%
“…When the nerve is blocked by cold or asphyxia, the depressor reflex is abolished first, and the persisting pressor reflex often becomes larger than before. Asphyxia, in contrast to cocaine, affects the largest fibres first [Clark et al 1935]: the effect of cold on fibres of different sizes is not so clearly known.…”
Section: Stimulation Of Normal Nervesmentioning
confidence: 99%
“…When cocaine, an agent which inactivates the smallest fibres first [Gasser, 1935], is applied to the nerve proximal to the point stimulated, the pressor reflex is abolished before the depressor reflex.…”
Section: Stimulation Of Normal Nervesmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments of Gasser & Erlanger [1929] suggest the former explanation; and there is direct evidence that the deformation caused by local pressure is most severe at the boundaries of the compressed part [Edwards & Cattell, 1928]. On the other hand, the experiments of Lewis, Pickering & Rothschild [1931] on man and those of Clark, Hughes & Gasser [1935] on animals showed that with quite low pressures a nerve in a limb may be blocked in from 16 to 40 min., and that ischaemia was the mechanism involved. These experiments have been confirmed by us [Bentley & Schlapp, 1943].…”
mentioning
confidence: 99%